Pooled human bone marrow-derived mesenchymal stromal cells with defined trophic factors cargo promote dermal wound healing in diabetic rats by improved vascularization and dynamic recruitment of M2-like macrophages - Willer, Hélène; Spohn, Gabriele; Morgenroth, Kimberly; Thielemann, Corinna; Elvers-Hornung, Susanne; Bugert, Peter; Delorme, Bruno; Giesen, Melanie; Schmitz-Rixen, Thomas; Seifried, Erhard; Pfarrer, Christiane; Schäfer, Richard; et al. (Frontiers in Immunology, 2022)
Human Mesenchymal Stromal Cells (hMSCs) are a promising source for cell-based therapies. Yet, transition to phase III and IV clinical trials is remarkably slow. To mitigate donor variabilities and to obtain robust and valid clinical data, we aimed first to develop a manufacturing concept balancing large-scale production of pooled hMSCs in a minimal expansion period, and second to test them for key manufacture and efficacy indicators in the clinically highly relevant indication wound healing. Our novel clinical-scale manufacturing concept is comprised of six single donor hMSCs master cell banks that are pooled to a working cell bank from which an extrapolated number of 70,000 clinical doses of 1x106 hMSCs/cm2 wound size can be manufactured within only three passages. The pooled hMSC batches showed high stability of key manufacture indicators such as morphology, immune phenotype, proliferation, scratch wound healing, chemotactic migration and angiogenic support. Repeated topical hMSCs administration significantly accelerated the wound healing in a diabetic rat model by delivering a defined growth factor cargo (specifically BDNF, EGF, G-CSF, HGF, IL-1α, IL-6, LIF, osteopontin, VEGF-A, FGF-2, TGF-β, PGE-2 and IDO after priming) at the specific stages of wound repair, namely inflammation, proliferation and remodeling. Specifically, the hMSCs mediated epidermal and dermal maturation and collagen formation, improved vascularization, and promoted cell infiltration. Kinetic analyses revealed transient presence of hMSCs until day (d)4, and the dynamic recruitment of macrophages infiltrating from the wound edges (d3) and basis (d9), eventually progressing to the apical wound on d11. In the wounds, the hMSCs mediated M2-like macrophage polarization starting at d4, peaking at d9 and then decreasing to d11. Our study establishes a standardized, scalable and pooled hMSC therapeutic, delivering a defined cargo of trophic factors, which is efficacious in diabetic wound healing by improving vascularization and dynamic recruitment of M2-like macrophages. This decision-making study now enables the validation of pooled hMSCs as treatment for impaired wound healing in large randomized clinical trials.